Sex-specific CT-derived muscle and fat phenotypes in colon cancer: implications for nutritional and metabolic assessment - Mucarzel, Fernanda; Peláez, Patricia Guirado; Utrilla, Virginia Soria; Jiménez, Rocío Fernández; Candia, Fiorella Palmas; Torralvo, Francisco José Sánchez; Peláez, Rosa Burgos; Almeida, José Manuel García; Olveira, Gabriel (Frontiers in Nutrition, 2025)
BackgroundComputed Tomography (CT)-derived analysis of Body Composition (BC) provides detailed phenotyping of skeletal muscle and adipose tissue, offering insight into nutritional and metabolic risk in oncology.ObjectiveTo characterize sex- and age-specific muscle and adipose tissue phenotypes in patients with colon cancer and describe their patterns across postoperative outcomes.MethodsMulticentric observational cross-sectional study including Colorectal Cancer (CRC) patients undergoing laparoscopic elective surgery. Preoperative CT scans at L3 were analyzed for muscle and adipose tissue quantity and radiodensity. Differences in BC parameters between patient groups (according to presence of complications, hospital stay and disease stage by sex) were assessed using Student’s t-test (p < 0.05).Results502 CRC patients, predominantly males (62.5%) with a mean age of 68.08 ± 10.62 were included. Sex-specific differences in muscle quality and adipose tissue distribution were observed across postoperative outcomes. In women, lower Subcutaneous Adipose Tissue (SAT) values were observed in those with longer hospital stay and complications (p < 0.001), whereas in men, reduced Skeletal Lean Muscle Radiodensity (p < 0.001) and higher Visceral Adipose Tissue (VAT; p = 0.013) were found in those with adverse outcomes. These differences were independent of BMI and age.ConclusionCT-based body composition phenotyping identifies distinct metabolic profiles linked to postoperative risk. Incorporating tissue quality and distribution into nutritional assessment may enhance early identification of vulnerable patients and guide personalized perioperative strategies.